Inisiasi dan pengembangan produk handsanitizer pada center of excellence Fakultas Farmasi Universitas Hasanuddin sebagai upaya pengembangan usaha intelektual kampus - Muhammad Raihan; Sandra Aulia Mardikasari; Subehan Lallo; Aliyah Putranto; Nana Juniarti Natsir Djide; Muhammad Akbar Bahar; Ismail Ismail; Andi Dian Permana; Yayu Mulsiani Evary; Abdul Rahim (Universitas Mataram, 2023)
PPUPIK is a community service program for 3 years. The purpose of this activity is to produce the intellectual products from the Faculty of Pharmacy UNHAS, especially Hand sanitizer and Disinfectant products, so that the Center of Excellence of the Faculty of Pharmacy UNHAS (CoE-FFUH) would become an independent business unit that able to support UNHAS' role as PTNBH. The specific target for this first year is the initiation of the development of a production unit of hand sanitizer and disinfectant products at CoE-FFUH. The initiation consists of the determination of documents for the production process, determination of product packaging material and designs, and also pilot-scale production for limited sales. As for the following year, hopefully, this product will be able to obtain a distribution permit for household health supplies (PKRT) so that the commercialization of licensed products can be carried out legally and able to produce more types of PKRT products.